Integrated evaluation of the requirements and excretions of Cu, Fe, Zn, and Mn for broilers via a uniform design method - Qiu, Kai; Chen, Zhimin; Chang, Wenhuan; Zheng, Aijuan; Cai, Huiyi; Liu, Guohua (Frontiers in Veterinary Science, 2023)
This study aimed to determine the ideal balance profile of Cu, Fe, Zn, and Mn for broilers of 1–21 days of age via a uniform experimental design. In Experiment 1, 900 1-day-old Arbor Acres male broilers were randomly allotted to 15 dietary treatments with six replicates of 10 birds. A total of 14 experimental diets were formulated with the supplementation of 8 16, 123 160, 40 80, and 60 120 mg/kg of Cu, Fe, Zn, and Mn, respectively, in the basal diet, according to the uniform design method. The excretion of Cu, Fe, Zn, and Mn in the manure and the broiler performance were determined to build the ideal balance profile of these elements. Experiment 2 was conducted based on the ideal balance profile built in Experiment 1, to test its practicability using 720 broilers with two treatments. The dietary concentrations of Cu, Fe, Zn, and Mn in the control group were 15.19, 203.08, 76.78, and 86.13 mg/kg, respectively. In Experiment 1, the concentrations of Cu, Fe, Zn, and Mn in the diets were 16.96, 166.66, 46.01, and 60.26 mg/kg, respectively, when the average daily gain reached the optimum value. When the dietary concentrations of Cu, Fe, Zn, and Mn were 8.54, 130.66, 38.19, and 64.07 mg/kg, respectively, the total excretion of Cu, Fe, Zn, and Mn got the minimum value. There are corresponding ideal balance profiles for minimum excretion of a certain element. In Experiment 2, the dietary levels of Fe, Zn, and Mn were decreased by 17.93%, 40.08%, and 30.04%, respectively, which had no significant effect on average daily gain, average daily feed intake, and feed gain for 1 21 day-old broilers but markedly decreased the excretion of Cu and Mn and total excretion. It was concluded that there is a dilemma between growth performance and mineral excretion. Although dietary levels of Cu, Fe, Zn, and Mn supporting optimal growth are higher than those for minimizing mineral excretion, supplementing too many trace elements in the diets of broilers is unnecessary.